A schematic framework for Life Cycle Assessment (LCA) and Green Building Rating System (GBRS). (June 2021) - Sartori, Thais; Drogemuller, Robin; Omrani, Sara; Lamari, Fiona
Abstract: Environmental Impact Assessment (EIA) tools link the environmental context of a building to the design decision-making framework. Life Cycle Assessment (LCA) and Green Building Rating Systems (GBRS) are the two approaches commonly used to holistically analyse the environmental performance of the whole building. While GBRS is mostly based on a checklist with many qualitative criteria, LCA compels decision-makers to base the analyses on numerical evidence, facilitating the comparison between design choices. Some GBRS, such as LEED, BREEAM and Green Star, have been incorporating LCA as part of their assessment system. This practice brings transparency to the design process and increases designers' awareness of the building's environmental impact. Consequently, this paper aims to develop a schematic EIA framework within the design life cycle, proposing future research directions to support its development. The framework was based in three parallel analyses: (1) comparison between LCA and GBRS assessment methodologies, (2) analysis of the LCA parameters within GBRS, and (3) investigation of LCA software tools focused on buildings that comply with GBRS requirements. The research found that, rather than performing either a GBRS or an LCA, the most appropriate EIA methodology will depend on the design life cycle stage. Graphical outputs and connection with 3D modelling will improve the evaluation of environmental impacts as a process integrated with the design. Highlights: The article synthesises the Life Cycle Assessment (LCA) requirements for Green Building Rating Systems (GBRS). It analyses building's specific LCA software tools recommended by GBRS, based on LCA standards requirements. It proposes a schematic framework to perform an Environmental Impact Assessment (EIA) throughout the design life cycle. It suggests future research directions to support the development of the proposed schematic framework.